Office price index lagging in Singapore and Hong Kong - Hui, Eddie Chi Man; Yu, Ka Hung; Ho, David Kim Hin (International Journal of Strategic Property Management, 2010)
Price discovery of real estate investment has been getting lots of attentions from researchers and it is generally believed that lagging errors exist in appraisal‐based returns of commercial real estate investments, in comparison to other investment instruments traded in the stock market. Due to fewer transactions in the commercial real estate market, it is reasonable to notice a difference in the handling of current market information. By introducing two study approaches along with a test case using Singapore's data, this paper explores the extent of lagging in Hong Kong's commercial (office) real estate values, in a State Space Model with Kaiman filter. The findings first suggest that whether appraisal‐based indices overstate or understate true values lies in the economy condition at the time. Then, commercial real estate values in Hong Kong are about three months behind the stock market property indices. Also, as indicated by the findings, data collection/selection bias may render a de‐lagged index not as efficient as it is supposed to be. This paper provides a different perspective on price discovery and the process of de‐lagging property values.First published online: 18 Oct 2010